Deep evolutionary roots of diet in seagrass bed fishes - Yangfan Chen; Zhaosong Chen; Jonathan S. Lefcheck; Qiang He (Reviews in Fish Biology and Fisheries, 2026)

Global Analysis of Shallow Underwater Fish Observation Research: 70 Years of Progress, Persistent Geographic Biases and a Path Forward - Angus John van Wyk; Rick D. Stuart‐Smith; Jordan S. Goetze; Eva Maire; Elodie Heyns‐Veale; Kaylee Smit; Tim J. Langlois; M. Aaron MacNeil; Alejandro Pérez‐Matus; Amanda T. Lombard; Ana Carolina; Christy Semmens; et al. (Fish and Fisheries, 2026)
Marine ecosystems are increasingly threatened by overfishing, pollution, coastal development and climate change, underscoring the need for long‐term, representative information on key fish populations and habitats to inform management and policy. Underwater fish observation (UFObs) techniques, such as Underwater Visual Census (UVC), stereo‐Baited Remote Underwater Video (stereo‐BRUV) and Remotely Operated Vehicles (ROVs), play a key role in sustaining long‐term data collection. Despite technological advancements, gaps persist in understanding research focus, geographic distribution and methodological biases inherent in these methods. We conducted a scientometric analysis of 1443 peer‐reviewed publications (1953–2023), employing natural language processing and network analysis to map the research landscape. We identified 15 knowledge clusters, including marine protected areas, apex predator conservation and reef ecosystems. Our findings reveal increasing use of BRUVS and ROVs in studies of marine protected areas and subsea infrastructure, while UVC remains prevalent in shallow coral reef research. Geographic representation is skewed, with the field dominated by researchers based in Australia and the United States, and underrepresented in Africa and Southeast Asia. This imbalance highlights the need for more inclusive, globally coordinated monitoring and reporting. Our results underscore the urgency of standardising protocols within each observation method and developing interoperable reporting frameworks across techniques to maximise data comparability and foster international collaboration. Addressing these challenges will strengthen the field's capacity to inform global conservation strategies and support sustainable fisheries management.

From kelp forests to turf reefs: Patterns, drivers, and impacts to functional diversity - Shane P. Farrell; Dara S. Yiu; Stuart K. Ryan; Rene D. Francolini; Courtney E. Stuart; Jonathan S. Lefcheck; Yasmina M. Shah Esmaeili; Douglas B. Rasher (Ecology, 2026)
Kelp forests are declining in many regions due to ocean warming, predator loss, and other anthropogenic stressors. In areas of rapid ocean warming, including the southern Gulf of Maine, these ecosystems have transitioned to a novel state dominated by low‐lying mats of turf algae. However, the pace, drivers, and ecological consequences of this transition remain unclear. Here, we used field surveys from 32 sites over 5 years (2018–2023) to reveal a continuation of kelp forest collapse and northward expansion of turf algae across Maine's coast. Next, we united data on benthic cover with key environmental variables in a structural equation model to show that turf algae were directly enhanced by higher ocean temperatures and decreased wave disturbance and indirectly enhanced by a warming‐induced loss of kelp cover. Lastly, we revealed the shift from kelp to turf yielded a seaweed assemblage dominated by traits associated with rapid growth, high surface area‐to‐volume ratios, and markedly reduced canopy height, indicating declines in habitat provisioning and carbon storage with kelp forest loss. Our findings highlight the accelerating impacts of climate change on temperate reef ecosystems and the vital services they provide. Further, we provide insights into a new state shift that is now occurring globally and underscore the need for urgent actions to mitigate further loss of foundational kelp forests.

Taking advantage of open data in coastal science and conservation - Nicholas M. Hoad; Jonathan S. Lefcheck; Nikolaos Alexandridis; Benjamin L.H. Jones; Johan S. Eklöf; Lina Mtwana Nordlund (Science of The Total Environment, 2025)

Biotic Mechanisms Strengthen Functional and Phylogenetic Convergence of Reef Fish Assemblages at Higher Latitudes - Nestor E. Bosch; Rick D. Stuart‐Smith; Katie May Laumann; Graham J. Edgar; Conor Waldock; J. Emmett Duffy; Jonathan S. Lefcheck (Journal of Biogeography, 2025)
Aim How communities of organisms come together has long fascinated scientists, with renewed interest in using functional and evolutionary patterns to infer mechanisms of community assembly. Ecological theory predicts that biotic interactions could lead to either divergence in the event of niche partitioning or convergence through the exclusion of competitively inferior species, but most macroecological studies attribute the latter to environmental influences. Here, we investigated the relative importance of these two opposing mechanisms across broad spatial gradients. We hypothesised stronger signals of: ( i ) convergence at high latitude owing to ecological generalism and ( ii ) divergence at low latitudes owing to specialisation. Major Taxa Studied Reef‐associated bony fishes. Location Global. Time Period 2006–2019. Methods We used a global dataset on marine reef fish assemblages comprising 2476 species at 3325 sites to disentangle the biotic drivers of community assembly across > 100° of latitude. We then applied a framework to remove environmental influences before examining whether any signs of biotic interactions remained in the trait and phylogenetic diversity of local communities relative to the (environmentally constrained) regional species pool, drawing on six functional traits and a phylogeny of bony fishes. Results Local fish assemblages were more functionally and phylogenetically similar to each other than expected based on the regional species pool at higher latitude reefs (i.e., show greater convergence). This pattern was evident after accounting for major sources of local environmental variation, suggesting exclusion of weak competitors. Functional convergence was mainly driven by traits related to resource acquisition, with high‐latitude assemblages converging towards more energetic carnivorous and planktivorous diets. Main Conclusions Our results suggest that biotic interactions drive greater trait and phylogenetic convergence from tropical to temperate zones. Likely mechanisms include increasing generalism and overlap in ecological strategies towards the poles, leading to the exclusion of weak competitors.

Implications of improved remote sensing capabilities on blue carbon quantification - Steven W.J. Canty; Miguel Cifuentes-Jara; Jorge Herrera-Silveira; Hannah K. Morrissette; Jordan R. Cissell; Joanna Acosta-Velázquez; Emil Cherrington; Ilka C. Feller; Daniel A. Friess; Jonathan S. Lefcheck; Loraé T. Simpson; Claudia Teutli-Hernandez (Estuarine, Coastal and Shelf Science, 2025)

Evaluating the effectiveness of field-based probiotic treatments for stony coral tissue loss disease in southeast Florida, USA - Kelly A. Pitts; Mackenzie Scheuermann; Jonathan S. Lefcheck; Blake Ushijima; Natalie Danek; E. Murphy McDonald; Aaron R. Milanese; Monica D. Schul; Julie L. Meyer; Kathryn A. Toth; Zachary Ferris; Yesmarie T. De La Flor; et al. (Frontiers in Marine Science, 2025)
Stony coral tissue loss disease (SCTLD) has spread throughout Florida’s Coral Reef, causing extensive mortality of over 30 species of reef-building corals, and has rapidly spread to many other countries and territories throughout the Caribbean. Current treatments for SCTLD, including a proprietary paste mixed with the antibiotic amoxicillin, do not provide protection from future infections and may select for antibiotic-resistant pathogenic bacteria. In contrast, beneficial microorganisms (i.e., probiotics), may directly treat or act as prophylactics for corals exposed to SCTLD. This study investigated the use of the bacterium Pseudoalteromonas sp. McH1-7, previously isolated from a SCTLD-resistant fragment of Montastraea cavernosa , as a potential probiotic treatment for SCTLD-infected M. cavernosa colonies in the wild. We developed and tested two probiotic deployment methods: (1) the injection of a probiotic in seawater suspension into a weighted bag placed over the coral to treat the whole colony; and (2) a sodium alginate-based paste that was applied directly to each disease lesion. After treatment, the disease progression of each colony was routinely monitored using three-dimensional photogrammetry for 2.5 years. Slurries of tissue and mucus samples were taken from healthy and diseased colonies before treatment, two weeks after treatment, and three months after treatment to identify possible shifts in bacterial and archaeal communities. McH1–7 successfully slowed SCTLD lesion progression for 2.5 years following treatments when delivered using the whole-colony treatment technique. Our assessment of the microbiome following treatment showed that McH1–7 was effective without dominating bacterial communities among infected corals. In contrast, corals treated with the probiotic paste lost more tissue than corals treated with the control paste, indicating that the lesion-specific probiotic paste is not effective at stopping SCTLD. Probiotic inoculations via a whole-colony treatment technique may provide a path toward slowing the loss of reef-building corals due to SCTLD.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

A Latitudinal Cline in the Taxonomic Structure of Eelgrass Epifaunal Communities is Associated With Plant Genetic Diversity - Collin P. Gross; J. Emmett Duffy; Kevin A. Hovel; Pamela L. Reynolds; Christoffer Boström; Katharyn E. Boyer; Mathieu Cusson; Johan Eklöf; Aschwin H. Engelen; Britas Klemens Eriksson; F. Joel Fodrie; John N. Griffin; et al. (Global Ecology and Biogeography, 2024)
Aim Biogenic structural complexity increases mobile animal richness and abundance at local, regional and global scales, yet animal taxa vary in their response to complexity. When these taxa also vary functionally, habitat structures favouring certain taxa may have consequences for ecosystem function. We characterised global patterns of epifaunal invertebrates in eelgrass ( Zostera marina ) beds that varied in structural and genetic composition. Location North America, Europe and Asia. Time Period 2014. Major Taxa Studied Peracarid crustaceans and gastropod molluscs. Methods We sampled epifaunal invertebrate communities in 49 eelgrass beds across 37° latitude in two ocean basins concurrently with measurements of eelgrass genetic diversity, structural complexity and other abiotic and biotic environmental variables. We examined how species richness, abundance and community composition varied with latitude and environmental predictors using a random forest approach. We also examined how functional trait composition varied along with community structure. Results Total species richness decreased with latitude, but this was accompanied by a taxonomic shift in dominance from peracarid crustaceans to gastropods, which exhibited different sets of functional traits. Greater eelgrass genetic diversity was strongly correlated with both richness and abundance of peracarids, but less so for gastropods. Main Conclusions Our results add to a growing body of literature that suggests genetic variation in plant traits influences their associated faunal assemblages via habitat structure. Because peracarids and gastropods exhibited distinct functional traits, our results suggest a tentative indirect link between broad‐scale variation in plant genetic diversity and ecosystem function.

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Interplay of management and environmental drivers shifts size structure of reef fish communities - Steven W. J. Canty; A. Justin Nowakowski; Courtney E. Cox; Abel Valdivia; Daniel M. Holstein; Benjamin Limer; Jonathan S. Lefcheck; Nicole Craig; Ian Drysdale; Ana Giro; Mélina Soto; Melanie McField (Global Change Biology, 2024)
Countries are expanding marine protected area (MPA) networks to mitigate fisheries declines and support marine biodiversity. However, MPA impact evaluations typically assess total fish biomass. Here, we examine how fish biomass disaggregated by adult and juvenile life stages responds to environmental drivers, including sea surface temperature (SST) anomalies and human footprint, and multiple management types at 139 reef sites in the Mesoamerican Reef (MAR) region. We found that total fish biomass generally appears stable across the region from 2006 to 2018, with limited rebuilding of fish stocks in MPAs. However, the metric of total fish biomass masked changes in fish community structure, with lower adult than juvenile fish biomass at northern sites, and adult:juvenile ratios closer to 1:1 at southern sites. These shifts were associated with different responses of juvenile and adult fish to environmental drivers and management. Juvenile fish biomass increased at sites with high larval connectivity and coral cover, whereas adult fish biomass decreased at sites with greater human footprint and SST anomalies. Adult fish biomass decreased primarily in Honduran general use zones, which suggests insufficient protection for adult fish in the southern MAR. There was a north–south gradient in management and environmental drivers, with lower coverage of fully protected areas and higher SST anomalies and coastal development in the south that together may undermine the maintenance of adult fish biomass in the southern MAR. Accounting for the interplay between environmental drivers and management in the design of MPAs is critical for increasing fish biomass across life history stages.

Blue carbon assessments of seagrass and mangrove ecosystems in South and Southeast Asia: Current progress and knowledge gaps - Milica Stankovic; Amrit Kumar Mishra; Yusmiana P. Rahayu; Jonathan Lefcheck; Daniel Murdiyarso; Daniel A. Friess; Marko Corkalo; Teodora Vukovic; Mathew A. Vanderklift; Syed Hilal Farooq; Juan Diego Gaitan-Espitia; Anchana Prathep (Science of The Total Environment, 2023)

Media myopia distorts public interest in US invasive plants - Elena Woodworth; Amy Tian; Kaleigh Blair; Jamie Pullen; Jonathan S. Lefcheck; John D. Parker (Biological Invasions, 2023)
Introduced invasive plants are a major environmental problem, but public interest in invasive plants is generally considered low compared to climate change and threatened flagship species, hindering support for effective management and policy. To understand what does drive public interest in invasive plants in the US, we investigated Google Trends search data from 2010 to 2020 for 209 introduced plant species found in the continental US. Using a phylogenetically-controlled structural equation model, we investigated three hypothesized drivers of interest: (1) plant abundance as quantified by national and state-level occurrence records in the Global Biodiversity Information Facility, (2) four key plant traits that might influence plant conspicuousness to the general public: ornamental use, human health risks, monoculture formation, and plants with positive economic value, and (3) media coverage, in particular the volume and sentiment of news articles over the same 10-year period. Public search interest was highest for the most abundant introduced species and those with human health risks, but significantly lower for ornamentals. News coverage was mostly negatively toned and disproportionately focused on a relatively small group of widespread invasive species, with significantly lower and more positively-worded coverage of ornamentals. Ultimately, we suggest that a narrow emphasis on a few highly covered ‘notorious’ invasive plant species, with lower and more positive coverage of ornamental introduced species, could send mixed messages and weaken public awareness of the threats of biological invasions. However, the generally strong linkages between public search interest and media coverage of invasive plants suggests ample opportunity to improve messaging and increase public awareness.

Belize Blue Carbon: Establishing a national carbon stock estimate for mangrove ecosystems - Hannah K. Morrissette; Stacy K. Baez; Lisa Beers; Nadia Bood; Ninon D. Martinez; Kevin Novelo; Gilbert Andrews; Luis Balan; C. Scott Beers; Sumeet A. Betancourt; Reynel Blanco; Eeryn Bowden; et al. (Science of The Total Environment, 2023)

Remote sensing for cost-effective blue carbon accounting - Martino E. Malerba; Micheli Duarte de Paula Costa; Daniel A. Friess; Lukas Schuster; Mary A. Young; David Lagomasino; Oscar Serrano; Sharyn M. Hickey; Paul H. York; Michael Rasheed; Jonathan S. Lefcheck; Ben Radford; et al. (Earth-Science Reviews, 2023)

Foundational biodiversity effects propagate through coastal food webs via multiple pathways - Aaron P. Ramus; Jonathan S. Lefcheck; Zachary T. Long (Ecology, 2022)
Relatively few studies have attempted to resolve the pathways through which the effects of biodiversity on ecosystem functioning cascade from one trophic level to another. Here, we manipulated the richness of habitat‐forming seaweeds in a western Atlantic estuary to explore how changes in foundation species diversity affect the structure and functioning of the benthic consumer communities that they support. Structural equation modeling revealed that macroalgal richness enhanced invertebrate abundance, biomass, and diversity, both directly by changing the quality and palatability of the foundational substrate and indirectly by increasing the total biomass of available habitat. Consumer responses were largely driven by a single foundational seaweed, although stronger complementarity among macroalgae was observed for invertebrate richness. These findings with diverse foundational phyla extend earlier inferences from terrestrial grasslands by showing that biodiversity effects can simultaneously propagate through multiple independent pathways to maintain animal foodwebs. Our work also highlights the potential ramifications of human‐induced changes in marine ecosystems.

Long-term Annual Aerial Surveys of Submersed Aquatic Vegetation (SAV) Support Science, Management, and Restoration - Robert J. Orth; William C. Dennison; Cassie Gurbisz; Michael Hannam; Jeni Keisman; J. Brooke Landry; Jonathan S. Lefcheck; Kenneth A. Moore; Rebecca R. Murphy; Christopher J. Patrick; Jeremy Testa; Donald E. Weller; et al. (Estuaries and Coasts, 2022)
Aerial surveys of coastal habitats can uniquely inform the science and management of shallow, coastal zones, and when repeated annually, they reveal changes that are otherwise difficult to assess from ground-based surveys. This paper reviews the utility of a long-term (1984–present) annual aerial monitoring program for submersed aquatic vegetation (SAV) in Chesapeake Bay, its tidal tributaries, and nearby Atlantic coastal bays, USA. We present a series of applications that highlight the program’s importance in assessing anthropogenic impacts, gauging water quality status and trends, establishing and evaluating restoration goals, and understanding the impact of commercial fishing practices on benthic habitats. These examples demonstrate how periodically quantifying coverage of this important foundational habitat answers basic research questions locally, as well as globally, and provides essential information to resource managers. New technologies are enabling more frequent and accurate aerial surveys at greater spatial resolution and lower cost. These advances will support efforts to extend the applications described here to similar issues in other areas.

Climate affects the outbreaks of a forest defoliator indirectly through its tree hosts - Kyle J. Haynes; Andrew M. Liebhold; Jonathan S. Lefcheck; Randall S. Morin; Guiming Wang (Oecologia, 2022)

Patterns of Consumption Across a Caribbean Seascape: Roles of Habitat and Consumer Species Composition Through Time - Carmen J. Ritter; Leah M. Harper; Jonathan S. Lefcheck; Valerie J. Paul; Ross Whippo; Scott Jones; Matthew B. Ogburn; J. Emmett Duffy (Frontiers in Marine Science, 2021)
Herbivores, omnivores, and predators transfer energy and structure the communities of many coastal marine ecosystems, and the intensity with which they consume prey and contribute to ecosystem functioning varies substantially among habitats over short time periods. Whether generalities across habitats might emerge for longer time series and using standard methods remains largely untested. Here, we deployed standardized assays of consumption using dried squid (“squidpops”) and five common macrophytes (“weedpops”) to quantify consumption across coral fore reef and patch reefs, mangroves, seagrass meadows, and bare sand from 2015 to 2019 around Carrie Bow Cay, Belize. We also used video in 2017 to identify the species responsible for consumption. We found that both squid- and weedpop consumption were consistently highest on patch and fore reef habitats, moderate in mangroves, and lowest in seagrass and sand across all years of the survey. Videos showed that the majority of consumption on the reefs in 2017 could be attributed to < 5 fish species, and the identity of the dominant consumers differed among habitats. This study validates a key but implicit assumption in marine ecology that relative patterns in consumption across habitats are consistent through space and time in tropical nearshore environments, and reveals that high consumption rates may be the consequence of one or few species in each location.

Optimizing Large-Scale Biodiversity Sampling Effort: Toward an Unbalanced Survey Design - Enrique Montes; Jonathan Lefcheck; Edlin Guerra Castro; Eduardo Klein; Ana Carolina de Azevedo Mazzuco; Gregorio Bigatti; Cesar Cordeiro; Nuno Simoes; Erasmo Macaya; Nicolas Moity; Edgardo Londoño-Cruz; Brian Helmuth; et al. (Oceanography, 2021)
Acquiring marine biodiversity data is difficult, costly, and time-consuming, making it challenging to understand the distribution and abundance of life in the ocean. Historically, approaches to biodiversity sampling over large geographic scales have advocated for equivalent effort across multiple sites to minimize comparative bias. When effort cannot be equalized, techniques such as rarefaction have been applied to minimize biases by reverting diversity estimates to equivalent numbers of samples or individuals. This often results in oversampling and wasted resources or inaccurately characterized communities due to undersampling. How, then, can we better determine an optimal survey design for characterizing species richness and community composition across a range of conditions and capacities without compromising taxonomic resolution and statistical power? Researchers in the Marine Biodiversity Observation Network Pole to Pole of the Americas (MBON Pole to Pole) are surveying rocky shore macroinvertebrates and algal communities spanning ~107° of latitude and 10 biogeographic ecoregions to address this question. Here, we apply existing techniques in the form of fixed-coverage subsampling and a complementary multivariate analysis to determine the optimal effort necessary for characterizing species richness and community composition across the network sampling sites. We show that oversampling for species richness varied between ~20% and 400% at over half of studied areas, while some locations were undersampled by up to 50%. Multivariate error analysis also revealed that most of the localities were oversampled by several-fold for benthic community composition. From this analysis, we advocate for an unbalanced sampling approach to support field programs in the collection of high-quality data, where preliminary information is used to set the minimum required effort to generate robust values of diversity and composition on a site-to-site basis. As part of this recommendation, we provide statistical tools in the open-source R statistical software to aid researchers in implementing optimization strategies and expanding the geographic footprint or sampling frequency of regional biodiversity survey programs.

Mangrove fragments as key coastal reservoirs of taxonomic and functional biodiversity - Guilherme N. Corte; Helio H. Checon; Yasmina Shah Esmaeili; Jonathan S. Lefcheck; A. Cecília Z. Amaral (Biodiversity and Conservation, 2021)

Habitat Primarily Structures Seagrass Epifaunal Communities: a Regional-Scale Assessment in the Chesapeake Bay - Claire E. Murphy; Robert J. Orth; Jonathan S. Lefcheck (Estuaries and Coasts, 2021)

Dissolved organic carbon sorption dynamics in tidal marsh soils - Andrew J. Pinsonneault; Patrick J. Neale; Maria Tzortziou; Elizabeth A. Canuel; Christina R. Pondell; Hannah Morrissette; Jonathan S. Lefcheck; James Patrick Megonigal (Limnology and Oceanography, 2021)
Coastal wetlands are significant sources of dissolved organic carbon (DOC) to adjacent waters and, consequently, exert a strong influence on the quantity and quality of DOC exported to the coastal oceans. Our understanding of the factors that control the exchange of DOC at the tidal marsh‐estuarine interface, however, remains limited. We hypothesize that tidal marsh soils act as a regulator and that their physical characteristics, such as organic carbon content and mineral phase composition, are key controls on DOC exchange between soil surfaces and both surface and interstitial waters. To test this hypothesis, we generated traditional Langmuir sorption isotherms using anaerobic batch incubations of four tidal wetland soils, representing a range of soil organic carbon content (1.77% ± 0.12% to 36.2% ± 2.2%) and salinity regimes (freshwater to mixoeuhaline), across four salinity treatments. Results suggest that the maximum soil sorption capacity and DOC binding affinity increase and decrease with greater salinity, respectively, though the enhancement of maximum soil sorption capacity is somewhat mitigated in soils richer in poorly crystalline iron minerals. Initial natively sorbed organic carbon showed a significant positive correlation with soil specific surface area and K showed a moderate yet significant positive correlation with poorly crystalline iron mineral content. Taken together, these results point to a strong mineralogical control on tidal marsh sorption dynamics and a complex physicochemical response of those dynamics to salinity in tidal marsh soils.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Boat Propeller Scarring of Seagrass Beds in Lower Chesapeake Bay, USA: Patterns, Causes, Recovery, and Management - Robert J. Orth; Jonathan S. Lefcheck; David J. Wilcox (Estuaries and Coasts, 2017)

Multiple stressors threaten the imperiled coastal foundation species eelgrass ( Zostera marina ) in Chesapeake Bay, USA - Jonathan S. Lefcheck; David J. Wilcox; Rebecca R. Murphy; Scott R. Marion; Robert J. Orth (Global Change Biology, 2017)
Interactions among global change stressors and their effects at large scales are often proposed, but seldom evaluated. This situation is primarily due to lack of comprehensive, sufficiently long‐term, and spatially extensive datasets. Seagrasses, which provide nursery habitat, improve water quality, and constitute a globally important carbon sink, are among the most vulnerable habitats on the planet. Here, we unite 31 years of high‐resolution aerial monitoring and water quality data to elucidate the patterns and drivers of eelgrass ( Zostera marina ) abundance in Chesapeake Bay, USA , one of the largest and most valuable estuaries in the world, with an unparalleled history of regulatory efforts. We show that eelgrass area has declined 29% in total since 1991, with wide‐ranging and severe ecological and economic consequences. We go on to identify an interaction between decreasing water clarity and warming temperatures as the primary drivers of this trend. Declining clarity has gradually reduced eelgrass cover the past two decades, primarily in deeper beds where light is already limiting. In shallow beds, however, reduced visibility exacerbates the physiological stress of acute warming, leading to recent instances of decline approaching 80%. While degraded water quality has long been known to influence underwater grasses worldwide, we demonstrate a clear and rapidly emerging interaction with climate change. We highlight the urgent need to integrate a broader perspective into local water quality management, in the Chesapeake Bay and in the many other coastal systems facing similar stressors.

Restored Eelgrass (Zostera marina L.) as a Refuge for Epifaunal Biodiversity in Mid-Western Atlantic Coastal Bays - Jonathan S. Lefcheck; Scott R. Marion; Robert J. Orth (Estuaries and Coasts, 2017)

Multitrophic functional diversity predicts ecosystem functioning in experimental assemblages of estuarine consumers - Jonathan S. Lefcheck; J. Emmett Duffy (Ecology, 2015)
The use of functional traits to explain how biodiversity affects ecosystem functioning has attracted intense interest, yet few studies have a priori altered functional diversity, especially in multitrophic communities. Here, we manipulated multivariate functional diversity of estuarine grazers and predators within multiple levels of species richness to test how species richness and functional diversity predicted ecosystem functioning in a multitrophic food web. Community functional diversity was a better predictor than species richness for the majority of ecosystem properties, based on generalized linear mixed‐effects models. Combining inferences from eight traits into a single multivariate index increased prediction accuracy of these models relative to any individual trait. Structural equation modeling revealed that functional diversity of both grazers and predators was important in driving final biomass within trophic levels, with stronger effects observed for predators. We also show that different species drove different ecosystem responses, with evidence for both sampling effects and complementarity. Our study extends experimental investigations of functional trait diversity to a multilevel food web, and demonstrates that functional diversity can be more accurate and effective than species richness in predicting community biomass in a food web context.

Biodiversity mediates top–down control in eelgrass ecosystems: a global comparative‐experimental approach - J. Emmett Duffy; Pamela L. Reynolds; Christoffer Boström; James A. Coyer; Mathieu Cusson; Serena Donadi; James G. Douglass; Johan S. Eklöf; Aschwin H. Engelen; Britas Klemens Eriksson; Stein Fredriksen; Lars Gamfeldt; et al. (Ecology Letters, 2015)
Nutrient pollution and reduced grazing each can stimulate algal blooms as shown by numerous experiments. But because experiments rarely incorporate natural variation in environmental factors and biodiversity, conditions determining the relative strength of bottom–up and top–down forcing remain unresolved. We factorially added nutrients and reduced grazing at 15 sites across the range of the marine foundation species eelgrass ( Zostera marina ) to quantify how top–down and bottom–up control interact with natural gradients in biodiversity and environmental forcing. Experiments confirmed modest top–down control of algae, whereas fertilisation had no general effect. Unexpectedly, grazer and algal biomass were better predicted by cross‐site variation in grazer and eelgrass diversity than by global environmental gradients. Moreover, these large‐scale patterns corresponded strikingly with prior small‐scale experiments. Our results link global and local evidence that biodiversity and top–down control strongly influence functioning of threatened seagrass ecosystems, and suggest that biodiversity is comparably important to global change stressors.

Physiological effects of diet mixing on consumer fitness: a meta‐analysis - Jonathan S. Lefcheck; Matthew A. Whalen; Theresa M. Davenport; Joshua P. Stone; J. Emmett Duffy (Ecology, 2013)
The degree of dietary generalism among consumers has important consequences for population, community, and ecosystem processes, yet the effects on consumer fitness of mixing food types have not been examined comprehensively. We conducted a meta‐analysis of 161 peer‐reviewed studies reporting 493 experimental manipulations of prey diversity to test whether diet mixing enhances consumer fitness based on the intrinsic nutritional quality of foods and consumer physiology. Averaged across studies, mixed diets conferred significantly higher fitness than the average of single‐species diets, but not the best single prey species. More than half of individual experiments, however, showed maximal growth and reproduction on mixed diets, consistent with the predicted benefits of a balanced diet. Mixed diets including chemically defended prey were no better than the average prey type, opposing the prediction that a diverse diet dilutes toxins. Finally, mixed‐model analysis showed that the effect of diet mixing was stronger for herbivores than for higher trophic levels. The generally weak evidence for the nutritional benefits of diet mixing in these primarily laboratory experiments suggests that diet generalism is not strongly favored by the inherent physiological benefits of mixing food types, but is more likely driven by ecological and environmental influences on consumer foraging.